Nilai Religius pada Kearifan Lokal Tembang Macapat Madura - Moh Hafid Effendy (UIN Sunan Gunung Djati Bandung, 2021)
The religious value of the local wisdom of the Madurese Macapat song is motivated by the variety of Madurese macapat songs that contain religious values which until now have been neglected by the Madurese ethnic in everyday life. This article examines the religious value of local Madurese wisdom in macapat songs. The method in this research uses a qualitative approach with a descriptive type. The techniques used in collecting data are through transcription, observation, documentation, and listening. Meanwhile, to analyze the data, researchers used identification, classification, and data description techniques. The results showed that the religious value of the local wisdom of the Madura macapat song contains the relationship between humans and God the creator of nature, namely Allah commands humans to carry out His good commands and stay away from His prohibitions. Meanwhile, the human-human relationship found symbolic meaning parèbhâsan with a reflection from Paul Recoer namely Kerras lamon ta’ akerrès which is intended for people who do not think before they act so that something happens less profitable for them. Madurese are advised to think before acting, so as not to be careless in doing something to others.